Objectification and Domination - Aleksy Tarasenko-Struc (Ergo, An Open Access Journal of Philosophy)
I resolve a tension between two prominent strands of feminist social critique. On the first, the domination of women consists largely in their objectification, and the objectifying character of such domination primarily explains why it is wrong. On the second, some salient forms of domination have a distinctively intersubjective dimension that makes them crucially unlike our standard modes of relating to objects. Yet in that case, how could characterizing these acts as objectifying capture why they are wrong? Focusing on domination that seeks recognition from the subordinate, I argue that each strand contains half the truth, weaving these together. The first is correct to point out that the concept of objectification is necessary for capturing the wrong of recognition-seeking domination, and that acts can be objectifying and ‘subjectifying’ all at once. The second strand is right to insist that domination of this sort has an irreducibly subjectifying character in light of which the concept of objectification is insufficient for clarifying its wrongness. The general lesson is that an account of the wrong of recognition-seeking domination is adequate only if it does justice to both its objectifying and subjectifying aspects.